Performance analysis of automotive air conditioning systems with electric compressors using R1234yf refrigerant: Insights into power consumption, cooling capacity, and energy efficiency - Mohd Zaki, Sharif; Azmi, W.H.; Ismail, Mohd. Farid; Awalludin, M.M.N.; Ghazali, M.F.; Amirullah, A.R.M. (2023)
R1234yf, a low global warming potential (GWP) refrigerant, offers a promising alternative to traditional refrigerants like R134a. This study analyzes automotive air conditioning systems (AAC) equipped with electric compressors and utilizing R1234yf refrigerant. The interrelationships between refrigerant charge, compressor speed, power consumption, cooling capacity, and energy efficiency are examined. The results show that increasing refrigerant charge and compressor speed leads to higher power consumption due to increased compressor work. However, higher refrigerant charges and compressor speeds improve cooling capacity in line with heat transfer principles. As refrigerant charge and compressor speed increase, the energy efficiency, measured by the Coefficient of Performance (COP), tends to decrease, indicating a trade-off between cooling capacity and energy efficiency. Optimizing refrigerant charge and compressor speed is crucial to strike a balance between cooling performance and energy efficiency. R134a outperforms R1234yf, with an average percent difference in COP approximately 25% higher at all compressor speeds. This study contributes to the understanding of AAC system performance and guides the development of energy-efficient automotive air conditioning. Future research can further explore system components and conditions to enhance energy efficiency and advance air conditioning technology.